Paired acute‐baseline serum tryptase levels in perioperative anaphylaxis: An observational study. Issue 6 (21st March 2019) - Vitte, Joana; Amadei, Laurent; Gouitaa, Marion; Mezouar, Soraya; Zieleskiewicz, Laurent; Albanese, Jacques; Bruder, Nicolas; Lagier, David; Mertès, Paul M.; Mège, Jean‐Louis; Schwartz, Lawrence B.; Leone, Marc
Abstract: Background: Anaphylaxis is recognized mainly through clinical criteria, which may lack specificity or relevance in the perioperative setting. The transient increase in serum tryptase has been proposed since 1989 as a diagnostic tool. Sampling for well‐defined acute and baseline determinations has been recommended. We assessed the performance of four proposed algorithms with tightly controlled time frames for tryptase sampling, their robustness with inadequate sampling times, and the possible use of mature tryptase determination. Methods: A retrospective study was performed on 102 adult patients from the Aix‐Marseille University Hospitals who had experienced a perioperative hypersensitivity reaction clinically suggesting anaphylaxis. EAACI and ICON criteria were used to diagnose anaphylaxis. Mature and total serum tryptase levels were measured. Results: Based on EAACI guidelines, clinical diagnostic criteria for anaphylaxis were found in 76 patients and lacking in 26. The most effective algorithm was the international consensus recommendation of 2012 that acute total tryptase levels should be greater than ([1.2×baseline tryptase] + 2] μg/L to be considered a clinically significant rise. In our cohort, this algorithm achieved 94% positive predictive value (PPV), 53% negative predictive value (NPV), 75% sensitivity, 86% specificity, and a Youden's index value of 0.61. A detectable acute mature tryptase level showed lower sensitivity, particularly in patients with acute total tryptase levels lower than 16 μg/L. Acute tryptase levels varied as a function of the clinical severity of anaphylaxis. Conclusion: Total tryptase levels in serum discriminated between nonanaphylactic and anaphylactic events in a perioperative setting when acute and baseline levels were collected and analyzed by the consensus algorithm. Abstract : The 2012 consensus that acute tryptase should be greater than [(1.2 × baseline tryptase) + 2] μg/L performs best among four algorithms for tryptase interpretation during perioperative anaphylaxis. The 2012 consensus that acute tryptase should be greater than [(1.2 × baseline tryptase) + 2] μg/L performs best for reaction grades 2, 3 and 4. Higher anaphylaxis grades are associated with higher levels of acute tryptase and more prevalent if baseline tryptase levels are above 5 μg/L. PPV: Positive predictive value; NPV: Negative predictive value